Digital Marketing Training To Increase The Visibility Of Pesantren Al Amalul Khair (Islamic Boarding School) - safrizal, safrizal; Nanda, Novira Fazri Nanda; Bella, Bella Putrie Nindyawan; Arif, Arif Nadzirul Haq E; Putri, Al Putri Oktavia; Indri, Indriani Indah Astuti; Donny , Donny Tirtana Afrizal; devi, Meeradevi Ravikumar (Jurnal Pengabdian kepada Masyarakat Nusantara, 2026)
In the digital era, Islamic boarding schools face significant challenges in promoting their programs and values due to low digital visibility and limited branding efforts. This community service initiative is designed to provide comprehensive digital marketing training aimed at increasing the online presence, engagement, and credibility of Islamic boarding schools. The primary goal is to improve the digital literacy and marketing capacity of Islamic boarding school administrators through structured training in social media management, content creation, digital branding, SEO, and performance analysis. The training includes interactive workshops, hands-on practice, mentoring, and ongoing evaluation, with key performance indicators such as at least a 50% increase in social media engagement, growth in followers, and higher new student interest through digital outreach within six months after the program. Quantitative evaluation using pre-test and post-test shows that participants’ competencies in digital marketing concepts, social media management, content creation, branding, and insight analysis increased in the “excellent” category, with several skill aspects improving by more than 100%. Qualitative indicators also demonstrate a rise in the number of participants confident in managing social media (from 10% to 90%) and able to create digital content (from 15% to 80%), as well as an increase in posting frequency to 3–4 times per week and the availability of formal branding guidelines. This program aligns with the national priority of digital transformation in education and community empowerment and proves effective in strengthening the professional, adaptive, and relevant image of Islamic boarding schools in the digital era.